Cross-Species Transmission of Bat Coronaviruses in the Americas: Contrasting Patterns between Alphacoronavirus and Betacoronavirus - Caraballo, Diego Alfredo (2022)
Bats harbor the largest number of coronavirus (CoV) species among mammals, serving as major reservoirs of alphaCoVs and betaCoVs, which can jump between bat species or to different mammalian hosts, including humans. Bat-CoV diversity is correlated with host taxonomic diversity, with the highest number of CoV species found in areas with the highest levels of bat species richness. Although the Americas harbor a unique and distinctive CoV diversity, no cross-species transmission (CST) or phylogeographic analysis has yet been performed. This study analyzes a large sequence data set from across the Americas through a Bayesian framework to understand how codivergence and cross-species transmission have shaped long-term bat-CoV evolution and ultimately identify bat hosts and regions where the risk of CST is the highest. Substantial levels of CST were found only among alphaCoVs. In contrast, cospeciation prevailed along the evolution of betaCoVs. Brazil is the center of diversification for both alpha and betaCoVs, with the highest levels of bat species richness. The bat family Phyllostomidae has played a key role in the evolution of American bat-CoVs, supported by the highest values of host transition rates. Although the conclusions drawn from this study are supported by biological/ecological evidence, it is likely that novel lineages will be discovered, which could also reveal undetected CSTs given that sequences are available from 11 of the 35 countries encompassing the Americas. The findings of this study can be useful for conducting targeted discovery of bat-CoVs in the region, especially in countries of the Americas with no reported sequences.